Severe Calciphylaxis Secondary to end Stage Renal Failure: A Case Report - Mohammad Isa, Muhammad Syafiq bin; Wan Ali, Wan Ahmad Syahril Rozli (UNUSA Press, 2023)
Calciphylaxis is a vascular calcification disease causing skin necrosis which contributes to high morbidity and mortality. Its exact pathogenesis is currently unknown but is commonly associated with chronic renal failure, hypercalcemia, hyperphosphatemia, secondary hyperparathyroidism and a variety of hypercoagulable state. It is relatively rare but may occur in 1-4% of patients with End Stage Renal Failure (ESRF).1 We are reporting a case of young lady with underlying ESRF presented with vascular and skin calciphylaxis.